British Government established this emergency hut on Heard Island in 1927, Antarctica, 1948 - Eastman, David, photographer; Australian News and Information Bureau (1948)
"... British Admiralty stores left for distressed mariners were still in good condtion when inspected by A.N.A.R.E. members."--Label on verso.
Title from label on verso.
Part of collection: Antarctica, Heard Island.
"L10031"--From label on verso.
Also available online
Keywords: Huts -- Antarctica -- Heard Island -- Photographs; Assistance in emergencies -- Antarctica -- Heard Island -- Photographs; Assistance in emergencies -- British -- Photographs; Heard Island (Heard and McDonald Islands) -- Photographs; Antarctica -- Australian -- Photographs